Memutus Penularan Kuman Penyakit Infeksi Saluran Cerna Melalui Penyuluhan Jamban Bersih dan Cuci Tangan Kepada Ibu-Ibu PKK RPTRA Harapan Mulya Jakarta - Rika Ferlianti; Ndaru Andri Damayanti; Endah Purnamasari (Majalah Sainstekes, 2018)
Diarrhea is an infectious disease which is a major cause of morbidityand mortality in the community. Diarrhea can be caused bygastrointestinal parasites, especially intestinal protozoa. Poor levels ofsanitation and low individual hygiene can lead to contamination of theinfective form of intestinal protozoa into food and drinks. The results ofpre-survey were at RPTRA Harapan Mulia in October 2016 that therewere still people in the settlements still not using personal latrines. Thelevel of cleanliness of mass latrines used collectively is still lacking.Latrines that are not managed properly are a description of sanitation aswell as poor hygiene so that it can disrupt the health of individuals andreduce work productivity and learning achievement. Counseling wascarried out to educate PKK group in Kelurahan Harapan Mulya, aboutthe habit of clean and healthy living through good latrine managementso as not to become a source of contamination into food and drinks, aswell as the correct way of washing hands. The extension method usedwas lectures and discussions with pre and post test assessment. Theextension activity was conducted one visit, on February 23, 2017. Totalrespondents were 27 people and had signed the approval sheet.Assessment of respondents' knowledge which is calculated from the valueof the pre and post test questionnaires shows results that increase by100%. At the end of the activity the respondent was given a leaflet on theprocedure for good hand washing and a kit for hand washing.